Correlation between lipid profile and C-reactive protein in children with nephrotic syndrome - Kurnia Dwi Astuti; Mohammad Heru Muryawan; Omega Mellyana (Indonesian Pediatric Society Publishing House, 2015)
Background Nephrotic syndrome (NS) causes dyslipidemia in children, which can be long term or intermittent. Dyslipidemia has long been established as a risk factor for atherosclerosis. An early sign of atherosclerosis is elevated high sensitivity C-reactive protien (hsCRP). Atherosclerosis early in life, especially in childhood, warrants an assessment for NS. Study on a correlation between lipid profile and hsCRP, as a marker of atherosclerosis, in pediatric NS patients has been limited. Objective To assess for a correlation between lipid profile and hsCRP in childhood nephrotic syndrome. Methods This cross-sectional study was undertaken on 29 children with NS in Dr. Kariadi Hospital. Serum hsCRP, total cholesterol, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) were examined in the active phase. Spearman's test was used to analyze a possible correlation between total cholesterol, LDL, HDL and hsCRP levels. Results Mean levels of total cholesterol (454 mg/dL) and LDL (288 mg/dL) in this study were high, while the HDL level (55 mg/dL) was normal, according to US Department of Health and Human Services classifications. The median hsCRP level was 0.33 mg/L and 9 (31%) subjects had high hsCRP levels of more than 1 mg/L. There was a positive correlation between LDL level and hsCRP (r=0.423; P<0.05). Conclusions There is a weak positive correlation between LDL and hsCRP levels in children with NS.